Vasculogenic mimicry structures in melanoma support the recruitment of monocytes. (31st December 2022) - Tan, Lih Y.; Cockshell, Michaelia P.; Moore, Eli; Myo Min, Kay K.; Ortiz, Michael; Johan, M. Zahied; Ebert, Brenton; Ruszkiewicz, Andrew; Brown, Michael P.; Ebert, Lisa M.; Bonder, Claudine S.
ABSTRACT: The progression of cancer is facilitated by infiltrating leukocytes which can either actively kill cancer cells or promote their survival. Our current understanding of leukocyte recruitment into tumors is largely limited to the adhesion molecules and chemokines expressed by conventional blood vessels that are lined by endothelial cells (ECs). However, cancer cells themselves can form their own vascular structures (a process known as vasculogenic mimicry (VM)); but whether they actively participate in the recruitment of leukocytes remains to be elucidated. Herein, we demonstrate that VM-competent human melanoma cell lines express multiple adhesion molecules (e.g. CD44, intercellular adhesion molecule (ICAM)-1 and junction adhesion molecules (JAMs)) and chemokines (e.g. CXCL8 and CXCL12) relevant for leukocyte recruitment. Microfluidic-based adhesion assays revealed that similar to ECs, VM-competent melanoma cells facilitate the rolling and adhesion of leukocytes, particularly monocytes, under conditions of shear flow. Moreover, we identified ICAM-1 to be a key participant in this process. Transwell assays showed that, similar to ECs, VM-competent melanoma cells facilitate monocyte transmigration toward a chemotactic gradient. Gene expression profiling of human melanoma patient samples confirmed the expression of numerous leukocyte capture adhesion molecules and chemokines. Finally, immunostaining of patient tissue microarrays revealed that tumors with high VM content also contained higher numbers of leukocytes (including macrophages). Taken together, this study suggests an underappreciated role of VM vessels in solid tumors via their active participation in leukocyte recruitment and begins to identify key adhesion molecules and chemokines that underpin this process.